Inulin prebiotic reinforces host cancer immunosurveillance via ɣδ T cell activation - Boucher, Emilie; Plazy, Caroline; Richard, Mathias L.; Suau, Antonia; Mangin, Irène; Cornet, Muriel; Aldebert, Delphine; Toussaint, Bertrand; Hannani, Dalil (Frontiers in Immunology, 2023)
The gut microbiota is now recognized as a key parameter affecting the host′s anti-cancer immunosurveillance and ability to respond to immunotherapy. Therefore, optimal modulation for preventive and therapeutic purposes is very appealing. Diet is one of the most potent modulators of microbiota, and thus nutritional intervention could be exploited to improve host anti-cancer immunity. Here, we show that an inulin-enriched diet, a prebiotic known to promote immunostimulatory bacteria, triggers an enhanced Th1-polarized CD4+ and CD8+ αβ T cell-mediated anti-tumor response and attenuates tumor growth in three preclinical tumor-bearing mouse models. We highlighted that the inulin-mediated anti-tumor effect relies on the activation of both intestinal and tumor-infiltrating γδ T cells that are indispensable for αβ T cell activation and subsequent tumor growth control, in a microbiota-dependent manner. Overall, our data identified these cells as a critical immune subset, mandatory for inulin-mediated anti-tumor immunity in vivo, further supporting and rationalizing the use of such prebiotic approaches, as well as the development of immunotherapies targeting γδ T cells in cancer prevention and immunotherapy.